Expression levels of th-2 and th-17 characteristic genes in healthy tissue versus periodontitis. - Parichehr Behfarnia; Reza Birang; Seyed Sajad Pishva; Mazdak Ghanjalikhani Hakemi; Mitra Mohammadi Khorasani (Tehran University of Medical Sciences, 2013)
The T helper 17 (Th17) cells have been suggested to have osteoclast activating effects while T helper 2 (Th2) cells are considered to have an osteoprotective role in periodontitis. This study was to compare the markers of Th17 cells (RORC2 and IL-17 genes) with that of Th2 cells (IL-4 and GATA-3 genes) between healthy and periodontitis tissues.The samples were obtained from patients with periodontitis and healthy tissues. The mRNA expression levels of IL-17, RORC2, IL-4 and GATA-3 were measured in both groups using quantitative RT-PCR. The results were compared using SPSS 11.0. Correlation coefficient was analyzed by Spearman's rho test. Mann-Whitney was used to measure the difference between IL-17 and IL-4 as well as RORC2 and GATA-3.In periodontal lesions, the expression levels of all markers were significantly higher than the healthy tissue (p≤ 0.001). The results showed a significant increase in the number of markers of Th17 (RORC2 and IL-17 genes) compared to markers of Th2 (GATA-3, IL-4) in patients with periodontitis compared to controls (p≤0.002). A positive correlation between IL-17 and RORC2 (p≤0.05) and between IL-4 and GATA-3 (p≤0.001) was found.The results show that expression levels of IL-4, GATA-3, IL-17 and RORC2 increase significantly in periodontal lesions compared with the controls. In periodontal lesions, IL-17 levels are significantly greater than IL-4, which plays a protective role against alveolar bone loss.